Biomarkers in metastatic renal cell carcinoma in the era of immune checkpoint inhibitors - Tripathi, Abhishek; Lin, Edwin; Agarwal, Neeraj (Annals of Translational Medicine, 2019)
Metastatic renal cell carcinoma (mRCC) accounts for around 74,000 new cases and 15,000 deaths annually in the United States alone (1). Until recently, sequential use of agents targeting the vascular endothelial growth factor (VEGF) or mechanistic target of rapamycin (mTOR) pathways were the cornerstone of therapy for the vast majority of patients (2).